2022
DOI: 10.21873/invivo.12780
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-based Prognostic Score as a Prognostic Biomarker in Patients With Recurrent and/or Metastatic Head and Neck Squamous Cell Carcinoma Treated With Nivolumab Therapy

Abstract: Background/Aim: The inflammation-based prognostic score (IBPS) has attracted attention recently as a prognostic biomarker for head and neck cancer patients. However, as the IBPS often changes after anticancer drug therapy, its independent prognostic value remains controversial. We aimed to investigate the relationship between the IBPS and prognosis in recurrent and/or metastatic head and neck squamous cell carcinoma (RMHNSCC) treated with nivolumab, and investigate changes in the IBPS before and after nivoluma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…In this context, GPS offers two advantages in clinical practice: ease of use with low cost and simultaneous reflection of the systematic nutritional and inflammatory status of patients with cancer [ 60 ]. In partial accordance with previous reports [ 22 , 23 , 24 , 25 , 26 ], our data found that patients with cancer and advanced GPS status were older, showed more betel quid use, and had decreased Hb levels, nutritional index (albumin, prealbumin, transferrin, and PNI), muscle mass, and histidine levels but higher levels of inflammatory markers (NLR and CRP), indicating a correlation between GPS, nutrition, and inflammation. Using the multivariate analysis that included all the possible confounding covariates, we further confirmed that advanced GPS outperformed other variables and was the sole prognostic factor for the 3-year mortality rate of patients with LAHNSCC ( Table 3 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this context, GPS offers two advantages in clinical practice: ease of use with low cost and simultaneous reflection of the systematic nutritional and inflammatory status of patients with cancer [ 60 ]. In partial accordance with previous reports [ 22 , 23 , 24 , 25 , 26 ], our data found that patients with cancer and advanced GPS status were older, showed more betel quid use, and had decreased Hb levels, nutritional index (albumin, prealbumin, transferrin, and PNI), muscle mass, and histidine levels but higher levels of inflammatory markers (NLR and CRP), indicating a correlation between GPS, nutrition, and inflammation. Using the multivariate analysis that included all the possible confounding covariates, we further confirmed that advanced GPS outperformed other variables and was the sole prognostic factor for the 3-year mortality rate of patients with LAHNSCC ( Table 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…These include old age [ 14 ], comorbidity [ 14 , 15 ], poor performance status [ 13 , 14 ], low body mass index (BMI) and body weight (BW) [ 13 , 14 , 16 ], anemia [ 14 , 15 ], low total lymphocyte count [ 13 ], low prognostic nutritional index (PNI) [ 17 ], high levels of C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) [ 18 , 19 , 20 ], and total muscle and fat mass [ 19 , 21 ]. In particular, the Glasgow prognostic score (GPS), an inflammation-based model that combines the levels of serum albumin and CRP, has demonstrated significance for predicting outcomes in patients with HNC under different clinical circumstances [ 22 , 23 , 24 , 25 , 26 ]. Patients with HNC or oropharyngeal squamous cell carcinoma who expressed a low pretreatment modified Glasgow prognostic score (mGPS) showed better survival outcomes than those who expressed a high mGPS [ 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the systemic in ammatory response (SIR) may play a critical role in tumor progression ,occurrence and metastasis by altering the tumor microenvironment, promoting angiogenesis and tumor cell proliferation [7,8].The peripheral blood cell counts, such as neutrophils, lymphocytes, monocytes or platelets can re ect the patient's immune and in ammatory statuses, which are associated with prognosis in many malignant tumors [9,10]. Neutrophil-to-lymphocyte ratio (NLR) is well-known as a systemic in ammation biomarker for various solid cancers, which integrates two in ammatory cells and is easily accessed from blood routine test [11][12][13][14][15]. Previous studies have demonstrated that NLR can predict the prognosis of patients with a variety of solid cancers, such as oesophageal squamous cell carcinoma, hepatocellular carcinoma, breast cancer and so on [14,16,17].…”
Section: Introductionmentioning
confidence: 99%